Productivity and quality of collection samples of pumpkin (Cucurbita L.) in the conditions of the southern forest-steppe of Western Siberia - N. G. Kazydub; Yu. A. Kashtanova (Овощи России, 2023)
Relevance. Currently, the priority direction in the development of the food industry is the use of local raw materials and the production of products with increased nutritional value, i.e. with an increased content of micronutrients, which include vitamins, minerals, macro and microelements. One of these products of plant origin is the pumpkin culture. The cultivation of high-yielding, versatile, nutrient-rich crops, such as pumpkin, plays an important role in ensuring food security. When breeding new improved varieties, special attention is paid to the adaptability of the crop to growing conditions, as well as to portion fruits with high taste and technological qualities.Purpose. Selection of the most adapted, productive, high-quality pumpkin samples for breeding and their cultivation in industrial production and the private sector in the conditions of the southern forest-steppe of Western Siberia.Material and methods. Field research was conducted in 2021-2022 at the experimental site of the selection (organic) crop rotation, in the educational and experimental farm of the Omsk State Agrarian University. Meteorological conditions during the years of the experiments were different, but quite typical for the climate of the southern forest-steppe of the Omsk region. The object of research are 5 varieties of large-fruited pumpkin: Dietary, Red etamp, Crumb, Honey crumb, Honey dessert; two samples of selection of the Omsk State Agrarian University: 1/15, 2/15; three samples of selection of the FGBOU IN RGAZU: 4/21, 5/21, 7/21. Observations, accounting and analysis were carried out according to generally accepted methods.Results. The biological yield of the studied cultivars varies from 10.3 to 42.2 t/ha in 2021 and from 18.2 to 35.8 t/ha in 2022.